Strategi Promosi Pariwisata Dalam Rangka Mempertahankan Objek Wisata Bamboo Rafting Loksado di Masa Pandemi COVID-19 (Studi Deskriptif Kualitatif pada Dinas Pemuda Olahraga dan Pariwisata Hulu Sungai Selatan) - Putri Ayu Hidayatur Rafiqoh (Sekolah Vokasi, Universitas Gadjah Mada, 2021)
The Covid-19 pandemic has had a major impact on Indonesia's tourism sector, including Hulu Sungai Selatan (HSS) Regency in South Kalimantan Province. HSS Regency has a potential tourist attraction that is a mainstay of South Kalimantan, namely the Bamboo Rafting Loksado tour. After having stopped operating due to the pandemic for 8 months, this tour was reopened by making changes to its operational system. This study aims to describe the tourism promotion strategy carried out by DISPORAPAR HSS in maintaining Bamboo Rafting tourism objects during the pandemic using descriptive qualitative research methods. DISPORAPAR HSS, which houses this tourist attraction, has compiled strategic steps to promote safe tourism for visitors by socializing the implementation of national health protocol standard based on the Indonesian Rafting Federation using educational videos on new normal tours, inviting local people to participate in supporting new normal tourism, using social media facilities as an effective and efficient means of promotion, and continuing to carry out the evaluation stages to realize Bamboo Rafting tourism objects to attract visitors again.